1998
DOI: 10.1557/s1092578300001010
|View full text |Cite
|
Sign up to set email alerts
|

Optical Properties of GaNAs Grown by MBE

Abstract: Optical properties of the GaNxAs1−x layers grown on (001) GaAs substrates by molecular beam epitaxy have been studied. The samples can be classified into three categories with respect to the concentration of N, as determined by x-ray diffraction and secondary-ion mass spectrometry: (i) with doping nitrogen concentration, (ii) with average content of N less than 30 %, and (iii) with x close to 100 %. From optical measurements of photoluminescence and Raman scattering, combined with analysis of x-ray diffraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The smaller size of N allows its solubility in GaAs and extensive research has been reported on such alloys [3][4][5][6][7][8]. In comparison, owing to the larger size of As and consequent difficulty in the incorporation of As in GaN, very limited work has been reported on N-rich side of GaAs x N 1−x alloys, which have been mostly prepared by MOCVD and MBE [9,10]. N-rich GaAs x N 1−x alloys are important materials for extending the wavelength range of GaNbased blue light emitting devices towards the red/infrared region.…”
Section: Introductionmentioning
confidence: 99%
“…The smaller size of N allows its solubility in GaAs and extensive research has been reported on such alloys [3][4][5][6][7][8]. In comparison, owing to the larger size of As and consequent difficulty in the incorporation of As in GaN, very limited work has been reported on N-rich side of GaAs x N 1−x alloys, which have been mostly prepared by MOCVD and MBE [9,10]. N-rich GaAs x N 1−x alloys are important materials for extending the wavelength range of GaNbased blue light emitting devices towards the red/infrared region.…”
Section: Introductionmentioning
confidence: 99%